2000
DOI: 10.1007/s10434-000-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence After Laparoscopic Radiofrequency Thermal Ablation of Hepatic Tumors

Abstract: LRFA has a 12% local failure rate, with larger adenocarcinomas and sarcomas at greatest risk. Failures occur early in follow-up, with most occurring by 6 months. LRFA seems to be a safe and effective treatment technique for patients with primary and metastatic liver malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0
9

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(125 citation statements)
references
References 23 publications
(26 reference statements)
6
110
0
9
Order By: Relevance
“…However, they also reported that there were no significant differences of overall and disease-free survival between surgical resection and rFA when the patients were in child-Pugh class B (8). the incidence of local failure after RFA was reported to be as low as 1.8%, but reached 12-18% as reported by other authors (21)(22)(23). In our department, the local recurrence rate after rFA is higher compared with that for surgery, but the difference is not significant (8.3 vs. 1.3%, p=0.13).…”
Section: Discussionsupporting
confidence: 48%
“…However, they also reported that there were no significant differences of overall and disease-free survival between surgical resection and rFA when the patients were in child-Pugh class B (8). the incidence of local failure after RFA was reported to be as low as 1.8%, but reached 12-18% as reported by other authors (21)(22)(23). In our department, the local recurrence rate after rFA is higher compared with that for surgery, but the difference is not significant (8.3 vs. 1.3%, p=0.13).…”
Section: Discussionsupporting
confidence: 48%
“…40 Our local recurrence rate of 3.6% after RFA of HCC is similar to local recurrence rates of 6% to 12% reported in recent surgical RFA series. 17,18 Currently, we are evaluating color flow Doppler ultrasonography with and without intravenously administered ultrasound contrast (Levovist, Schering Plough, Kenilworth, NJ) to determine whether this technique will improve our accuracy in monitoring the zone of coagulative necrosis induced by RFA, thus reducing the incidence of incomplete treatment and local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the tumor location, RFA can be performed laparoscopically or percutaneously [125,126,127,128,129,130]. Existing data report on all kinds of endocrine tumors.…”
Section: Locoregional Ablative Therapymentioning
confidence: 99%